Infrastructures of flow: streaming media as elemental media. Issue 2 (15th March 2022) - Grandinetti, Justin; Ingraham, Chris
ABSTRACT: Streaming media are often placed in a lineage of electrical technologies that promise connectivity at a distance. We argue, however, that the material-discursive entanglement of streaming is a technological descendent of pre-electrical attempts to control essential resources through flow. Inspired by John Durham Peters's emphasis on elemental media, we examine streaming media practices that date to antiquity in order to assess infrastructures of flow today. By considering material technologies that capture and channel critical resources to be the "original" streaming media, we demonstrate how the idealized metaphor of streaming conceals the imbrication of human–technology–nature that underpins the capture and channel of flows. Consequently, we position streaming media as infrastructural, indebted to environments, and as part of a lineage that includes not only the telegraph, telephone, television, and film, but also rivers, canals, aqueducts, and pipelines.